1986
DOI: 10.1126/science.232.4750.619
|View full text |Cite
|
Sign up to set email alerts
|

A Mid-Brunhes Climatic Event: Long-Term Changes in Global Atmosphere and Ocean Circulation

Abstract: A long-term climatic change 4.0 x 10(5) to 3.0 x 10(5) years ago is recorded in deep-sea sediments of the Angola and Canary basins in the eastern Atlantic Ocean. In the Angola Basin (Southern Hemisphere) the climatic signal shows a transition to more humid ("interglacial") conditions in equatorial Africa, and in the Canary Basin (Northern Hemisphere) to more "glacial" oceanic conditions. This trend is confirmed by comparison with all well-documented marine and continental records from various latitudes availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
152
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(157 citation statements)
references
References 38 publications
5
152
0
Order By: Relevance
“…Again, this explanation cannot be excluded, but it may be difficult to push back the onset of the fast oscillating glacial cycle into the Cenozoic. Instead, we suggest that Middle and Upper Pleistocene strandlines are well identified from one another thanks to the fast oscillating sea level that follows the mid-Brunhes event (Jansen et al, 1986) with a periodicity of 100,000 years, as indicated by the isotopic record (Lisiecki and Raymo, 2005). Earlier than this event, sea-level oscillations were seemingly of smaller amplitudes and faster wavelengths (40,000 yrs cycle).…”
Section: Apparent Uplift Rates and Geodynamicsmentioning
confidence: 99%
“…Again, this explanation cannot be excluded, but it may be difficult to push back the onset of the fast oscillating glacial cycle into the Cenozoic. Instead, we suggest that Middle and Upper Pleistocene strandlines are well identified from one another thanks to the fast oscillating sea level that follows the mid-Brunhes event (Jansen et al, 1986) with a periodicity of 100,000 years, as indicated by the isotopic record (Lisiecki and Raymo, 2005). Earlier than this event, sea-level oscillations were seemingly of smaller amplitudes and faster wavelengths (40,000 yrs cycle).…”
Section: Apparent Uplift Rates and Geodynamicsmentioning
confidence: 99%
“…Farrell and Prell (1991) suggested that a 600-kyr Brunhes Dissolution Cycle (BDC) be superimposed on glacial/ interglacial 100-kyr cycles during the Late Pleistocene in the central equatorial Pacific. The BDC is clearly apparent as a lower-frequency envelope on the 100-kyr cycles (Barker et al 2006;López-Otálvaro et al 2008), being observed in a wide variety of marine and continental records (e.g., Jansen et al 1986). On a longer timescale, pelagic CaCO 3 production was proposed to reveal a primary candidate driver for the BDC representing apparent mid-Brunhes dissolution (MBD) or the mid-Brunhes event (MBE), but its cause remains unknown (Pisias and Rea 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The MBE, characterized by a more zonal circulation in the Northern Hemisphere, was terminated by a global southward migration of polar and subtropical fronts (Jansen et al 1986). As such, more glacial conditions became prevalent in the Northern Hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…(See the section dealing with the stratigraphy.) This core has rather constant MARS of ca 0.60 g cm-* ka-' for the interval 3-7 m below the core top and 0.21 g cm-* ka-' for the upper 3 m [15,47]. In the lower interval, short-term increases of terrigenous input are indicated by the presence of quartz and mica grains and of a few turbiditic laminae.…”
Section: Dating With 'Obementioning
confidence: 99%